Réponses

2013-11-20T21:33:27+01:00
Phi = (1+racine(5))/2

phi² = (1+racine(5))²/4 = (1+2racine(5)+5)/4

phi+1 =   (1+racine(5))/2 + 1

si phi²=phi+1, alors:

(1+2racine(5)+5) - (1+racine(5)) - 1 = 0
-----------------------    -----------------
             4                            2

(1+2racine(5)+5) - (2+2racine(5)) - 4 = 0
-----------------------    ------------------     ----
             4                           4                 4


(1+2racine(5)+5) - (2+2racine(5)) - 4 = 0

1 + 2racine(5) + 5 - 2 - 2racine(5) - 4 = 0

0 = 0

Les 2 membres sont égaux, donc la condition est bonne.

          1                            (1+racine(5))/2 - 1
---------------------     =      --------------------------
 (1+racine(5))/2                         1

(1+racine(5))/2 * ( (1+racine(5))/2 - 1) = 1